The analogy method for the description of external characteristic of inner combustion engines - Stonys, Agnius; Sapragonas, Jonas; Mockus, Saulius (Transport, 2004)
The original data for the evaluation of vehicle motion dynamics is external characteristic of its engine, which consists of three parameters: torque, power and specific fuel consumption. It is very important to have the dependences of these characteristics on revs for various engine load cases, creating a vehicle model under real motion conditions. Load cases are defined by a load coefficient. Car‐makers usually don't declare full engine external characteristics, which overtake all load coefficient variation interval. The purpose of this article is to research, how to get full description of engine torque function without its full data. The analogy method, which is used in polymers and composites mechanics, was employed for the description of a torque function. The method is based on the creation of summarized characteristic, making horizontal and vertical shifts of torque dependences. From the curve it is possible to get a proper characteristic at a chosen load coefficient.First Published Online: 27 Oct 2010